Food safety in Africa and strategic directions for improving policy and regulatory frameworks - Grace, Delia; Alonso, Silvia; Roesel, Kristina; Covic, Namukolo M.; McDermott, John J. (2019)
Foodborne diseases (FBD) and associated food safety concerns and associated impose health and economic burdens and indirectly affect the development and flourishment of domestic and export food sectors in Africa. Because these impacts are large, they will compromise the attaining of the Sustainable Development Goals and the commitments of the Malabo declaration unless FBD in Africa are brought under control. Food safety concerns will become of even greater importance as developments advance towards a free trade zone for the continent. Promoting food safety systems becomes necessary.